Fish waste to sustainable additives: Fish protein hydrolysates alleviate intestinal dysbiosis and muscle atrophy induced by poultry by-product meal in Lates calcarifer juvenile - Chaklader, Md Reaz; Howieson, Janet; Foysal, Md Javed; Hanif, Md Abu; Abdel-Latif, Hany M.R.; Fotedar, Ravi (Frontiers in Nutrition, 2023)
Valorising waste from the processing of fishery and aquaculture products into functional additives, and subsequent use in aquafeed as supplements could be a novel approach to promoting sustainability in the aquaculture industry. The present study supplemented 10% of various fish protein hydrolysates (FPHs), obtained from the hydrolysis of kingfish (KH), carp (CH) and tuna (TH) waste, with 90% of poultry by-product meal (PBM) protein to replace fishmeal (FM) completely from the barramundi diet. At the end of the trial, intestinal mucosal barriers damage, quantified by villus area (VA), lamina propria area (LPA), LPA ratio, villus length (VL), villus width (VW), and neutral mucin (NM) in barramundi fed a PBM-based diet was repaired when PBM was supplemented with various FPHs (p < 0.05, 0.01, and 0.001). PBM-TH diet further improved these barrier functions in the intestine of fish (p < 0.05 and 0.001). Similarly, FPHs supplementation suppressed PBM-induced intestinal inflammation by controlling the expression of inflammatory cytokines (tnf-α and il-10; p < 0.05 and 0.001) and a mucin-relevant production gene (i-mucin c; p < 0.001). The 16S rRNA data showed that a PBM-based diet resulted in dysbiosis of intestinal bacteria, supported by a lower abundance of microbial diversity (p < 0.001) aligned with a prevalence of Photobacterium. PBM-FPHs restored intestine homeostasis by enhancing microbial diversity compared to those fed a PBM diet (p < 0.001). PBM-TH improved the diversity (p < 0.001) further by elevating the Firmicutes phylum and the Ruminococcus, Faecalibacterium, and Bacteroides genera. Muscle atrophy, evaluated by fiber density, hyperplasia and hypertrophy and associated genes (igf-1, myf5, and myog), occurred in barramundi fed PBM diet but was repaired after supplementation of FPHs with the PBM (p < 0.05, 0.01, and 0.001). Similarly, creatine kinase, calcium, phosphorous, and haptoglobin were impacted by PBM-based diet (p < 0.05) but were restored in barramundi fed FPHs supplemented diets (p < 0.05 and 0.01). Hence, using circular economy principles, functional FPHs could be recovered from the fish waste applied in aquafeed formulations and could prevent PBM-induced intestinal dysbiosis and muscular atrophy. GRAPHICAL ABSTRACT